The Legal Cancellation Consequences of A Notarial Deed Due to The Elements Existence of Unlawful Acts (Case Study of Supreme Court Ruling Number 20 PK/PID/2020) - Andriani, Ayu (JURNAL AKTA, 2024)
As a public official, a Notary has the task of making deeds. The deed is an authentic piece of evidence to prove that a legal action has occurred between the two parties. Every authentic deed made by a Notary creates legal certainty. Therefore, notaries are required to always be careful and thorough in carrying out their official duties. However, in practice, in carrying out their duties, quite a few Notaries experience problems related to the deeds they make. Like the case that occurred in Supreme Court Decision Number 20 Pk/Pid/2020. Where the Notary is proven to have committed an unlawful act in making the deed and this results in the deed being invalidated. The cancellation of the notarial deed will result in the agreement between the two parties being no longer binding and all processes of transferring rights based on the deed becoming invalid and deemed to have never occurred. For this reason, it is hoped that notaries will always apply the principle of prudence, uphold dignity and professional code of ethics so that they remain wise in carrying out their official duties without harming any party.